2021
DOI: 10.1002/ddr.21901
|View full text |Cite
|
Sign up to set email alerts
|

Terbutaline attenuates LPS ‐induced injury of pulmonary microvascular endothelial cells by cAMP /Epac signaling

Abstract: Acute lung injury (ALI), characterized by an acute onset of severe hypoxemia, is a common and devastating syndrome usually triggered by lipopolysaccharide (LPS) infection from bacteria. This study is intended to explore whether terbutaline can alleviate LPS‐induced human pulmonary microvascular endothelial cell (HPMVEC) injury through cAMP/Epac signaling. LPS was utilized to induce ALI in HPMVECs, and after exposure of LPS‐induced HPMVECs to terbutaline, the cellular functions including cell viability and apop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…cAMP has long been considered to be an inducer of anti-inflammatory responses (Tavares et al 2020). In fact, multiple investigations have demonstrated that the cAMP signaling pathway in many cells had a role in controlling LPS-induced ALI (Duan et al 2022;Wang et al 2022a). However, it still remains to be explored whether these pathways are modified by m6A methylation.…”
Section: Discussionmentioning
confidence: 99%
“…cAMP has long been considered to be an inducer of anti-inflammatory responses (Tavares et al 2020). In fact, multiple investigations have demonstrated that the cAMP signaling pathway in many cells had a role in controlling LPS-induced ALI (Duan et al 2022;Wang et al 2022a). However, it still remains to be explored whether these pathways are modified by m6A methylation.…”
Section: Discussionmentioning
confidence: 99%
“…The activation of dendritic cell by salbutamol encourages CD4 + T cells to secrete IL-10 ( Hervé et al, 2017 ). Through activating cAMP/Epac signaling, terbutaline protects pulmonary microvascular endothelial cells from LPS-induced damage ( Duan et al, 2022 ). (R)-salbutamol significantly suppressed LPS-induced polarization of M1 macrophages and decreased the expression of M1 typical cytokines through down-regulating the metabolism of aerobic glycolysis and glycerophospholipid ( Wang et al, 2020c ).…”
Section: Bronchodilators As Potential Therapeutic Options For Covid-19mentioning
confidence: 99%
“…The combination of dexamethasone with formoterol or salmeterol resulted in rapid relief of respiratory symptoms (Weber et al, 2020) 5. Suppressing the polarization of M1 macrophages as well as the expression of M1 macrophage's typical cytokines, including MCP-1, IL-1β and TNF-α (Duan et al, 2022) 6. Action on cAMP/Epac signaling (Hervé et al, 2017) Anticholinergic drugs Ipratropium 1.…”
Section: Side Effects Of Bronchodilatorsmentioning
confidence: 99%
“…The literature suggests the use of AZD3199 (inhaled ultra-long-acting β₂-adrenoceptor agonist), which has a higher safety profile than formoterol, with a very low incidence of adverse effects that may be related to its lower level of systemic side effects, as well as in combination with fluticasone propionate inhalation aerosol and tiotropium bromide powdered inhalation or with other glucocorticosteroid inhalers and M-receptor blocking agents [18]. Glucocorticoid inhalers inhibit the release of inflammatory mediators from the airway, suppressing the body's inflammatory response and improving airway function, and M receptor blockers reversibly inhibit M cholinergic receptors, causing smooth muscle relaxation [19,20]. The M receptor blocker reversibly inhibits the M cholinergic receptor, causing smooth muscle relaxation.…”
Section: The Choice Of Inhalant For This Patientmentioning
confidence: 99%